From the Lab to the Market - PHILLIPS, ANDELKA; Charbonneau, Jan (Council for Responsible Genetics, 2015)
With traditional genetic testing, doctors collect DNA samples, explain test results and advise patients on treatment options. With direct-to-consumer (DTC) genetic testing, private companies provide genetic tests and results in commercial transactions. Consumers provide DNA samples directly to DTC genetic testing companies, with results provided back directly to consumers, typically online and usually without involving doctors.[1] Direct-to-consumer genetic tests range from health-related tests with significant healthcare implications (e.g. disease predisposition) to the so-called recreational genomics with no discernible implications (e.g. earwax consistency).[2] Of particular concern has been the offering of health-related tests outside the traditional medico-legal environment. Questions have been raised about the quality of health-related direct-to-consumer genetic tests and whether results are understandable by the average consumer. Concern has also been expressed about the appropriate regulation of the DTC genetic testing industry; at present DTC genetic testing purchases are normally governed by corporate contract and privacy policies. It is questionable whether consumers are giving valid consent for the tests and participation in DTC genetic testing research. Finally, there is a consensus that consumers often have insufficient understanding that the terms and conditions they agree to on DTC genetic testing websites (when they click "I agree") are legally binding agreements.
Keywords: direct-to-consumer genetic testing; consumer protection; genetic privacy; clickwrap contract; Digital Humanities; Genes & Society; Identities in Transformation; Online Privacy; Privacy Law; clickwrap contract; computer-assisted language learning; data privacy; direct-to-consumer genetic testing; genetic privacy; Policy